Agents with Principles: The Control of Labor in the Dutch East India Company, 1700 to 1796. (October 2017) - Wezel, Filippo Carlo; Ruef, Martin
Principal-agent problems plagued early modern corporations. The existing literature emphasizes the potential benefits provided by private trade in aligning the interests of company agents to those of their principals. We contribute to this line of work by analyzing the organizational and social mechanisms that may help address principal-agent problems in the presence of private trading opportunities. Drawing on personnel records of more than half a million seafarers employed by the Dutch East India Company (VOC) over nearly a century, we show that monitoring was effective in reducing desertion when private trade was conceived as a market activity subordinated to hierarchy. Social bonds were more effective in preventing desertion when the company elevated private trade above hierarchy. Our analysis clarifies how early corporations could maintain control over a geographically dispersed and diverse labor force in the absence of modern tools of organizational governance.